Profitability, Liquidity, Leverage, and Earnings Growth (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Earnings Growth is still an interesting issue to research, without exception in the food and beverage industry. The purpose of this study is to determine the factors that are thought to influence earning growth in food and beverage companies listed on the Indonesia Stock Exchange with an observation period of 2015-2018. The research method used is Panel Data Regression Analysis and the results show that only Net Profit Margin (NPM) and Current Ratio (CR) affect Earning Growth (EG) while the Debt to Asset Ratio (DAR) does not affect on Earning Growth. (EG).